2019
DOI: 10.1177/1937586718796590
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Patient and Staff Outcomes With Inpatient Unit Designs Incorporating Decentralized Caregiver Workstations: A Systematic Review of Empirical Evidence

Abstract: Objectives: This systematic literature review synthesizes and assesses quality of research addressing associations of patient and staff outcomes with inpatient unit designs incorporating decentralized caregiver workstations. Background: A current hospital design trend is to include decentralized caregiver workstations on inpatient units. A review of literature addressing decentralized unit design is needed. Methods: The systematic review methodology was guided by the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…While the 2008 literature review found that decentralized nursing stations increased staff effectiveness (by reducing staff walking time and increasing patient‐care time), 25 a more recent systematic review of the available empirical evidence found mixed results, with inconsistent findings for decentralized designs. The review went on to say that the literature on the topic was “of very low quality and show[ed] inconsistency in associated outcomes.” 26 Design characteristics, for example, were found to be diverse among studies, with a range of architectural solutions lacking standard definitions for decentralized nursing stations or consistent categorization of nursing‐station type. While much has been written about the effect of the built environment on human experience, even perception, the impact of the built environment on burnout and staff turnover remains largely unexplored.…”
Section: Case Study: Design For Outcomes In Hospital Carementioning
confidence: 99%
“…While the 2008 literature review found that decentralized nursing stations increased staff effectiveness (by reducing staff walking time and increasing patient‐care time), 25 a more recent systematic review of the available empirical evidence found mixed results, with inconsistent findings for decentralized designs. The review went on to say that the literature on the topic was “of very low quality and show[ed] inconsistency in associated outcomes.” 26 Design characteristics, for example, were found to be diverse among studies, with a range of architectural solutions lacking standard definitions for decentralized nursing stations or consistent categorization of nursing‐station type. While much has been written about the effect of the built environment on human experience, even perception, the impact of the built environment on burnout and staff turnover remains largely unexplored.…”
Section: Case Study: Design For Outcomes In Hospital Carementioning
confidence: 99%
“…Early survey item development was based on a review of existing post occupancy surveys in healthcare settings, and leaned particularly on the Center for the Built Environment Occupant Toolkit [ 48 , 49 ]. Survey items underwent further iteration in response to research questions explored, and gaps identified, in the literature examining clinical caregivers’ relationship to the healthcare built environment [ 50 , 51 ]. The initial survey items were written to assess the key nurse activities and interactions identified in the literature, which included nurse walking fatigue, charting, ability to spend time with patients, and teamwork, especially in emergent situations.…”
Section: Methodsmentioning
confidence: 99%
“…Research indicates that social support from others can settle work stress, reduce depression, and positively impact patient outcomes (Alvaro et al, 2016). Numerous studies have revealed that job satisfaction is influenced by work environment, unit layout, nursing care delivery model, organizational climate, and interpersonal relationships (Jimenez et al, 2019; Obeidat et al, 2021). Ulrich’s (1991) theory of supportive design grounds this in noting that the physical environment will reduce stress if it fosters perceptions of control and social support.…”
Section: Review Of the Literaturementioning
confidence: 99%